Peran Guru Pendidikan Pancasila dan Kewarganegaraan dalam Penguatan Karakter Kreatif Siswa Kelas XII di SMK Islam Al Madina Kecamatan Pecangaan Kabupaten Jepara - Fatma, Lukiyah; Karim, Abdul; Rinenggo, Alil (WASPADA (Jurnal Wawasan Pengembangan Pendidikan), 2025)
Pancasila and Citizenship Education teachers have a strategic role in strengthening the creativecharacter of students at SMK Islam Al Madina Pecangaan District, Jepara Regency. This study aims todescribe the role of Pancasila and Citizenship Education Teachers in strengthening the creative character ofclass XII students at SMK Islam Al Madina. This research uses a qualitative approach with descriptivemethods. Data collection techniques using observation, interviews, and documentation. The results showedthat the teacher of SMK Islam Al Madina towards strengthening the creative character of students has a roleas: 1) facilitator, providing opportunities for students to express their ideas and providing learningreferences; 2) motivator, providing encouragement to students to express ideas; 3) manager, using severalmethods such as lectures, group discussions and assignments to students so that students are able to generateideas; 4) guide, guide students to read diligently and be confident in expressing ideas; 5) demonstrator, hasnot been implemented optimally because the teacher does not have varied learning media; 6) evaluator, usesseveral assessments (oral tests, independent assignments, presentations) which are used as a reference forthe level of student understanding; 7) role model, the teacher has not maximized his role as a role modelbecause he shows more discipline character to students. Researchers used six indicators of creativecharacter, namely 1) fluency; 2) flexibility; 3) originality; 4) elaboration; 5) high curiosity; 7) like to try newthings.Keywords: Role of Pancasila and Civic Education Teacher, Strengthening, Creative Character